Less would be the answer for both i think :P im late XD
Answer:
![2ab - 6a + 5b - 15](https://tex.z-dn.net/?f=2ab%20-%206a%20%2B%205b%20-%2015)
Step-by-step explanation:
Given
![2ab - 6a + 5b + \_](https://tex.z-dn.net/?f=2ab%20-%206a%20%2B%205b%20%2B%20%5C_)
Required
Fill in the gap to produce the product of linear expressions
![2ab - 6a + 5b + \_](https://tex.z-dn.net/?f=2ab%20-%206a%20%2B%205b%20%2B%20%5C_)
Split to 2
![(2ab - 6a) + (5b + \_)](https://tex.z-dn.net/?f=%282ab%20-%206a%29%20%2B%20%285b%20%2B%20%5C_%29)
Factorize the first bracket
![2a(b - 3) + (5b + \_)](https://tex.z-dn.net/?f=2a%28b%20-%203%29%20%2B%20%285b%20%2B%20%5C_%29)
Represent the _ with X
![2a(b - 3) + (5b + X)](https://tex.z-dn.net/?f=2a%28b%20-%203%29%20%2B%20%285b%20%2B%20X%29)
Factorize the second bracket
![2a(b - 3) + 5(b + \frac{X}{5})](https://tex.z-dn.net/?f=2a%28b%20-%203%29%20%2B%205%28b%20%2B%20%5Cfrac%7BX%7D%7B5%7D%29)
To result in a linear expression, then the following condition must be satisfied;
![b - 3 = b + \frac{X}{5}](https://tex.z-dn.net/?f=b%20-%203%20%3D%20b%20%2B%20%5Cfrac%7BX%7D%7B5%7D)
Subtract b from both sides
![b - b- 3 = b - b+ \frac{X}{5}](https://tex.z-dn.net/?f=b%20-%20b-%203%20%3D%20b%20-%20b%2B%20%5Cfrac%7BX%7D%7B5%7D)
![- 3 = \frac{X}{5}](https://tex.z-dn.net/?f=-%203%20%3D%20%5Cfrac%7BX%7D%7B5%7D)
Multiply both sides by 5
![- 3 * 5 = \frac{X}{5} * 5](https://tex.z-dn.net/?f=-%203%20%2A%205%20%3D%20%5Cfrac%7BX%7D%7B5%7D%20%2A%205)
![X = -15](https://tex.z-dn.net/?f=X%20%3D%20-15)
Substitute -15 for X in ![2a(b - 3) + 5(b + \frac{X}{5})](https://tex.z-dn.net/?f=2a%28b%20-%203%29%20%2B%205%28b%20%2B%20%5Cfrac%7BX%7D%7B5%7D%29)
![2a(b - 3) + 5(b + \frac{-15}{5})](https://tex.z-dn.net/?f=2a%28b%20-%203%29%20%2B%205%28b%20%2B%20%5Cfrac%7B-15%7D%7B5%7D%29)
![2a(b - 3) + 5(b - \frac{15}{5})](https://tex.z-dn.net/?f=2a%28b%20-%203%29%20%2B%205%28b%20-%20%5Cfrac%7B15%7D%7B5%7D%29)
![2a(b - 3) + 5(b - 3)](https://tex.z-dn.net/?f=2a%28b%20-%203%29%20%2B%205%28b%20-%203%29)
![(2a + 5)(b - 3)](https://tex.z-dn.net/?f=%282a%20%2B%205%29%28b%20-%203%29)
The two linear expressions are
and ![(b - 3)](https://tex.z-dn.net/?f=%28b%20-%203%29)
Their product will result in ![2ab - 6a + 5b - 15](https://tex.z-dn.net/?f=2ab%20-%206a%20%2B%205b%20-%2015)
<em>Hence, the constant is -15</em>
Answer:
5
Step-by-step explanation:
Edge i think dont quote me on this plz
He needs 3 Tickets to Win a Prize.27×2 is... And that's ur Answer